PEMANFAATAN FILTRASI SEDERHANA PENJERNIH SUMBER AIR RUMAH TANGGA SEBAGAI AIR BAKU KELURAHAN PIDADA KOTA BANDAR LAMPUNG - Ergantara, Rani Ismiarti; Marsad, Hardoyo; Atmono, Atmono; Dwicahya, Vina (Program Studi Manajemen Fakultas Ekonomi dan Manajemen Universitas Malahayati, 2022)
: Stunting is a condition of failure to thrive in children under five (babies under 5 years old) due to chronic malnutrition, so that children are too short for their age. Malnutrition occurs while the baby is in the womb and in the early postnatal period after the baby is born; however, the stunting condition only appears after the baby is 2 years old. According to Ministry of Health (2018) research, stunting can be caused by poor nutrition (40%), a lack of clean water, and poor sanitation (60%). Clean water is one of the basic human needs to meet healthy living standards. In the Pidada neighborhood itself, there is still a lack of access to clean water, and the problem related to clean water is that there is a lime substance contained in the water. The goal of this activity is to provide the community with solutions for turning dirty water into clean water through the use of filtration. Twenty people from the Pidada Village community participated in Posyandu activities. The results of the implementation of activities where the community is enthusiastic and can understand the criteria for clean water also indicate that the community can also understand the right simple filtration techniques. This can be seen from the many questions and the number of residents who want to try the simple filtration props that have been designed. The simple filtration props demonstrated were made from plastic bottles with a volume of 1.5 liters. Through the socialization method of this activity, it is hoped that it can raise public awareness about improving and maintaining the quality of clean water and also be a solution to the problem of clean water in Pidada Village, which can prevent stunting for the Golden Generation launched by the government.